The Impact of Student Motivation on Students’ Science Process Skills - Perdana, Rahmat; Asrial; Maison (Journal of Education Research and Evaluation, 2022)
Learning motivation is an encouragement for someone to be more active in achieving something. However, everyone’s motivation is different so that it affects students’ science process skills. This study aims to describe the effect of students’ learning motivation on students’ science process skills in learning science. This study uses a sequential explanatory approach. The research subjects were 175 class VIII students who were selected by total sampling technique. The data collection instruments used were observation sheets for students’ science process skills, student learning motivation questionnaires, and interview sheets. Qualitative data were analyzed using Miles and Hubarman while quantitative data were analyzed using descriptive and inferential statistics using assumption and hypothesis testing (regression test) to see the effect of learning motivation on students’ science process skills. The results of this study conclude that there is a significant effect of students’ learning motivation on students’ science process skills with a significance value of 0.001. Learning outcomes have implications for the learning process, namely as an evaluation material to create effective learning. Science process skills of students will increase along with the high motivation of students in learning. The results of this study can contribute to the world of education in particular and society in general. Through the results of this study, it is known how students’ learning motivation and the level of students’ science process skills in science learning, as well as knowing the relationship between learning motivation and students’ science process skills.